Resolution from the trustees of Cullenswood House to the INAAVD in favour of donating Cullenswood house and Glanmire property to Margaret Pearse, - Cullenswood House (Dublin, Ireland) (1918)
Resolution signed by Laurence Nugent, Clifford V. Mcgloughlin and John M. Ford.